The influence of midsole shear on running economy and smoothness with a 3D-printed midsole - Clermont, C.; Barrons, Z. B.; Esposito, M.; Dominguez, E.; Culo, M.; Wannop, J. W.; Stefanyshyn, D. (Sports Biomechanics, 2023)
The objectives of this study were to first determine whether a newly designed 3D-printed midsole, configured with a mechanism to increase anterior-posterior deformation, could increase anterior midsole shear during the stance phase of running. We then wanted to determine whether these shoes could affect running economy and smoothness. Two footwear conditions, differing in midsole technology, were used in this study. The control condition consisted of a thermoplastic polyurethane midsole (TPU-Control), whereas the prototype shoes (3D-Shear) were constructed with a 3D-printed lattice midsole designed for greater anterior foot displacement during early to mid-stance. Twenty male participants ran on a treadmill for 6 min in each condition, and data were collected during the final 2 min. Midsole shear was measured using 3D kinematic data; running smoothness was quantified with peak acceleration and jerk magnitudes from the foot, sacrum, and head; and running economy was determined with oxygen consumption data. As hypothesised, the anterior midsole shear was greater in the 3D-Shear condition compared to the TPU-Control. The 3D-Shear did not improve running economy. Runners exhibited significantly lower peak accelerations at the sacrum, along with lower magnitudes of jerk at the foot, sacrum, and head in the 3D-Shear condition, indicating smoother running patterns.